Effect of Sodium Hydroxide on The Tensile Properties of Sugar Palm Fibre Reinforced Thermoplastic Polyurethane Composites - A. A., Mohammed; Bachtiar, Dandi; Siregar, J. P.; M. R. M., Rejab (Faculty Mechanical Engineering, UMP, 2016)
Global warming, environmental changes, and other problems have been increasing in the last decade. Researchers and scholars want to safeguard life on the earth by making ecofriendly products, like natural composite materials. Natural fibre is environmentally valuable because of its biodegradable nature. However, there is a serious problem caused by the incompatibility between fibre and matrix. In this work, sugar palm fibre was combined with thermoplastic polyurethane composites after treatment with different concentrations of sodium hydroxide from 2 to 6% to enhance the compatibility between them. An extrusion machine was used to combine 30% by weight of the sugar palm fibre and 70% by weight of thermoplastic polyurethane composites. The temperature, rotation velocity, and fibre size were fixed at (180–190–200°C), 40 rpm and 250 µm respectively. The composite was characterized according to ASTM D638. The sodium hydroxide treatment of the fibre could provide a good tensile modulus of 440 MPa at 2% of NaOH, and strain of 41.6% at 6% NaOH of the composite. However, the tensile strength was decreased, where the highest amount of 5.49 MPa recorded at 6% NaOH. Meanwhile, the tensile modulus and strain of the composites are found to be much better than those of untreated ones. In contrast, the tensile strength was still not improved.